Simulation Analysis of Surrounding Rock Stability of Three-dimensional Cross Underground Cavern Group - ZHOU Yong; ZHANG Shuai; PAN Bing; CAI Bo; WU Jiang (Renmin Zhujiang)
In order to meet the needs of stable construction excavation and normal operation of the main transformer room of Yangfanggou hydropower station,multiple caverns were excavated on its right wall,such a three-dimensional cross cavern group is formed.In order to study the surrounding rock stability of cavern group,according to the actual geological conditions and construction schedule on site,this paper conducts a three-dimensional numerical simulation analysis of the entire construction process of the cavern group by the FLAC3D program,obtains the distribution characteristics of the surrounding rock deformation,stress and plastic zone of the cavern group,and based on these,evaluates the rationality and surrounding rock stability of the excavation scheme of the three-dimensional cross cavern group,which provide scientific basis and technical guidance for excavation and support design.